ANALISIS KANDUNGAN SENYAWA MINYAK KAYU PUTIH HASIL PRODUKSI PERUSAHAAN PERSEORANGAN LOKAL DAN PERUSAHAN PERDAGANGAN MENGGUNAKAN KROMATOGRAFI GAS-SPEKTROSKOPI MASSA (KG-SM) - Kirana Efruan, Gian (Yayasan Akrab Pekanbaru, 2018)
Cajuput oil has several different constituent components. The compounds of cajuput oil component which becomes the main standard of quality assessment in this study is the percentage of cineole compound. In Indonesia, oils with a concentration of 1.8 sineol over 55% are considered as first quality oils, and those below this value are considered as standard oils. The conventional method used in this study to analyze the compounds of the cajuput oil component is Gas Chromatography-Mass Spectroscopy (GC-MS). By using GC-MS on Product A, Product B, and Product C, it shows that there are 13 compounds identified as the compounds composing cajuput oil in each product and the percentage of the content of each compound is also varied. The content of the main compound of cajuput oil in product A (product from private company) and C (product from trading company) is sineol compound of 72,11% and 53,17%, while in Product B (product from private company), the main compound is Î±-pinene of 61.92%. The results of the analysis also shows that the content of cineole as the main compound of the cajuput oil in Product A and Product C has met the quality standard of SNI 06-3954-2006, while Product B has not. Key words: cajuput oil, cineole, GC-MS, The compounds of cajuput oil component